Pengembangan Alat Bantu Material handling untuk Meminimasi Beban Kerja Operator Produksi Crank Case di PT.X - Theopilus, Yansen; Jonathan, William; Gustin, Yusan (Universitas Katolik Parahyangan, 2018)
This research aims to evaluate the workload of production operators at PT. X and develop a product/tools that can minimize the workload of production operators in PT.X factory. PT.X is a motorcycle manufacture company that produces sport bike, duck bike, and scooter bike along with its components. One of the main components produced in PT. X is crankcase. Crankcase function as a house for motorcycle machine components such as generator, oil pumps, clutches, crankshaft, transmission gear, and lubricating oil. This research focuses on crankcase production because the crankcase production operators have the most complaints regarding workload compared to others.The research begins by evaluating the workload of the operators on the initial working system. The evaluation data is collected by some method such as direct field observation, direct measurement, and interview with the operators. After that, the data is processed to evaluate the mental and physical workload of the operators using NIOSH, RULA, and NASA-TLX methods. The Evaluation results show that there are several operators that have an excessive workload, especially for the material handling work. This activity results Lifting Index value of more than 1, a RULA value of more than 5, and a NASA-TLX value greater than 80.Based on the evaluation, this research developed a material handling tool in the form of workpiece basket lifting equipment using a combination of pneumatic and hydraulic principles that can minimize the workload of the crankcase production operator at PT. X. This tool can eliminate a bending movement which is the source of problem in the operators workload. The result of the evaluation of this tool application shows that the use of the tool can produce a reasonable workload for all crankcase production operators at PT. X.